Participation of pregnant women in pregnancy exercise: The role of knowledge, attitudes, and husband's support - Sembiring, Imelda; Liena, Liena; Suyono, Tan; Lister, Clarissa; Suwarno, Suwarno; Sulistijanto, Eddy (Jurnal Prima Medika Sains, 2024)
Pregnancy exercise offers numerous benefits for both mother and child. However, many pregnant women do not participate in this activity. This study aims to identify factors influencing pregnant women's participation in pregnancy exercise at Darussalam Health Center, Medan City. A cross-sectional study was conducted on 60 pregnant women visiting the Darussalam Health Center. Data were collected using a structured questionnaire and analyzed using Chi-square tests and logistic regression. The findings indicate that most pregnant women did not participate in pregnancy exercise. Knowledge of the benefits of prenatal exercise, positive attitudes toward exercise, and partner support were significant predictors of participation. Multivariate analysis confirmed that these three factors were independently associated with exercise participation. This study highlights the importance of knowledge, attitudes, and partner support in promoting prenatal exercise among pregnant women. Health education programs focusing on these factors could encourage more women to engage in regular physical activity during pregnancy.